2018
DOI: 10.1111/anu.12825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multienzyme complex and probiotic supplementation on the growth performance, digestive enzyme activity and gut microorganisms composition of snakehead (Channa argus)

Abstract: The major objective of this study conducted for 7 weeks was to investigate the influence of supplementation with multienzyme complex and probiotic and their interaction effects on the growth performance, body composition, serum biochemical parameters and gut microorganism composition of snakehead (Channa argus). There were four treatments in this experiment coded as control, probiotic (Bacillus amyloliquefaciens), multienzyme (amylase, acid protease and papain) and pro‐multi (B. amyloliquefaciens and amylase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The results showed no difference in moisture and ash content in all treatments (P >0.05). Similar results were discovered in L. vannamei (Adel et al 2017), parrotfish (Liu et al 2017), and snakehead (Dai et al 2018).…”
Section: Discussionsupporting
confidence: 85%
“…The results showed no difference in moisture and ash content in all treatments (P >0.05). Similar results were discovered in L. vannamei (Adel et al 2017), parrotfish (Liu et al 2017), and snakehead (Dai et al 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Higher content of total protein in the PR group and higher levels of total protein and albumin in the PR and EN-PR groups were detected after 45 days. Inoculation of probiotics to diet has been reported to improve the utilization of protein in the gut, thus resulting in a higher synthesis of protein in the liver and a higher content of protein in serum (Dai et al, 2019;Vazirzadeh et al, 2020). Fish in the PR and EN-PR groups had higher levels of total protein and albumin compared to fish in the PC group after exposure to lead at all intervals, which may be attributed to the protective effects of the probiont used against leadinduced liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Because of low cost and efficient, the production proportion of enzyme in the feed industry increased gradually. The potential of different kind of exogenous enzymes as green feed additives had been discussed in correlational studies, while the beneficial effects on growth performance and feed utilization of terrestrial animals and aquatic animals had been demonstrated (Dai, Hou, Hou, & Qian, ; Kholif, Abdo, Anele, El‐Sayed, & Morsy, ; Liu, Wu, Li, Duan, & Wen, ; Salem, Gado, Colombatto, & Elghandour, ; Wang, Xu, et al, ; Zhu, Wen, Li, Xuan, & Li, ). In the present study, the addition of 1.5 g/kg EC had the best effect on the final weight, the weight gain rate, the specific growth rate and the feed conversion of the Japanese seabass, which was consistent with the results of Lin, Mai, and Tan () who found that the specific growth rate and feed utilization of tilapia ( Oreochromis niloticus × O. aureus ) were significantly improved by the supplementation of 1.5 g/kg EC composed of neutral protease, β‐glucanese and xylanase.…”
Section: Discussionmentioning
confidence: 99%